Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar IPAS di Kelas V SD Inpres Sanrangan Kabupaten Gowa: Student Learning Outcomes, Implementation of Problem Based Learning. - Muchsin, Muh Afiq; Amir Pada; Widya Karmila Sari Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
jThe problem in this study is the low learning outcomes of fifth grade students of SDInpres Sanrangan, Gowa Regency. This study aims to determine:(1) Problem BasedLearning Model on Science Learning Outcomes, (2) Student learning outcomes inthe subject of Science, (3) The Effect of the Application of Problem Based Learningon Science Learning Outcomes. The approach used in this study is quantitative witha quasi-experimental design research type. The data collection techniques used arequestionnaires, observation and documentation. The data analysis technique usedis by conducting hypothesis testing using a t-test with the Independent sample t-testtype. The results of the study showed that the learning process by implementing theApplication of Problem Based Learning at each meeting increased. Students'interest in learning after being given treatment in the form of the Application ofProblem Based Learning increased. The probability value obtained from the resultsof the hypothesis test analysis is less than 0.05 so it is concluded that there is asignificant difference between the post non-test of the experimental class and thecontrol class. The conclusion in this study is that the Application of Problem BasedLearning has a positive effect. Students' interest in learning before being giventreatment was in the category of less interested, and after being given treatment inthe form of the Application of Problem Based Learning, students' interest in learningincreased. There is an effect of the Application of Problem Based Learning onstudent learning outcomes.